Methylxanthines: Potential Therapeutic Agents for Glioblastoma - Pérez-Pérez, Daniel (Pharmaceuticals (Basel), 2019)
Glioblastoma (GBM) is the most common and aggressive primary brain tumor. Currently, treatment is ineffective and the median overall survival is 20.9 months. The poor prognosis of GBM is a consequence of several altered signaling pathways that favor the proliferation and survival of neoplastic cells. One of these pathways is the deregulation of phosphodiesterases (PDEs). These enzymes participate in the development of GBM and may have value as therapeutic targets to treat GBM. Methylxanthines (MXTs) such as caffeine, theophylline, and theobromine are PDE inhibitors and constitute a promising therapeutic anti-cancer agent against GBM. MTXs also regulate various cell processes such as proliferation, migration, cell death, and differentiation; these processes are related to cancer progression, making MXTs potential therapeutic agents in GBM.